Aplikasi Pemantauan Posisi Anak-Anak Menggunakan Smart Watch dan Database Firebase - Indrayana, I Nyoman Eddy; Sutawinaya, I Putu; Yasa, Kadek Amerta; Pratiwi, Ni Made Wirasyanti Dwi (Jurnal Ilmu Komputer; Vol 12 No 2 (2019): Jurnal Ilmu KomputerDO - 10.24843/JIK.2019.v12.i02.p06, 2019)
Child safety is a concern for parents in this modern era. Crime against children often threatens them, when parental supervision is weak. Parents cannot monitor at all times the activities of their children. Parents have little time to monitor their children's activities because they are busy with their work, especially their children who are still sitting in kindergartens and elementary schools. Parents need a tool or application that can help monitor the position of children at all times. For this purpose, an application for monitoring the position of children was built using the Smartwatch and Firebase realtime database. The making of software in this study uses the Unified Software Development Process (USDP) method which has 4 phases of work namely Inception, Elaboration, Construction and Transition. This software involves 2 actors namely "child" actor and "parent" actor. The "child" actor will send latitude and longitude positions through the smartwatch he uses. Actors "parents" will see the child's position in a map on the mobile screen in realtime.